Application of Vulkan technology for 3D Visualization of large computing data which change over the time - Mustafin, M. B.; Akhmed-Zaki, D. Zh; Turar, O. N. (Vestnik KazNU. Serii͡a︡ matematika, mekhanika, informatika, 2019)
In this work, a high-performance app for visualization of large-size grid models (about a million cells) with using of Vulkan technologies was developed. Vulkan is a new software interface (API) which controls the graphic processor (GPU). Vulkan became a low-level API, thanks to which the entire GPU capability was used, such as memory and synchronization control, error checking, creation of commands performed by graphic processor, etc. Thus it shows high performance with less load on the CPU. For the operation of the application without interruption, double buffering of vertex buffer and multi-threading of the processor was used. The results of Poisson’s equation, namely data of each iteration, were taken for the 2D and 3D model visualization. Using of the above given methods, the Poisson’s equation grid model examples are given. As a result of this work, a prototype of a visualizer was developed and presented, and it can be used for any results of numerical mathematical modeling on structured and unstructured 3D grids.